KARAKTERISTIK DAN PEMANFAATAN BATUAN SERPENTINIT DI DESA UEKULI KABUPATEN TOJO UNA-UNA PROVINSI SULAWESI TENGAH - Botjing, Muslimin U. (Jurnal Sains dan Teknologi Tadulako, 2025)
Serpentinite rock is one of the mineral sources of magnesite this is known by the considerable content of the element magnesium (Mg). Testing the physical and chemical properties of serpentinite rocks found in certain locations is considered to have considerable prospects to be utilized and developed. The research was conducted in Uekuli Village Tojo Una-Una Regency Central Sulawesi Province using X-Ray Diffraction (XRD) and X-Ray Flourescence (XRF) methods. The results of XRD analysis obtained 4 types of minerals in the ST 02 test sample namely olivine as much as 3.4% lizardite 72.4% forsterite 18.6% and orthopyroxine as much as 5.6%. While at station 09 2 minerals were obtained namely lizardite 97.5% while hematite was 2.5%. Meanwhile based on the results of XRF testing the ST 02 sample has a dominant compound of MgO as much as 42.754% and SiO2 as much as 43.185%. Similarly the ST 09 sample has a dominant compound of MgO as much as 39.314% and SiO2 as much as 40.866%. In the analysis results it can be seen that the content of Al2O3 and K2O is quite low while the content of MgO and Fe2O3 is quite high. The high content of MgO and SiO2 is a characteristic of serpentinite rocks where serpentinite rocks are rich in magnesium and silica.